Effect of e-cigarette advertisements and antismoking messages on explicit and implicit attitudes towards tobacco and e-cigarette smoking in 18–65-year-olds: a randomised controlled study protocol. Issue 6 (23rd June 2017) - Booth, Paula; Albery, Ian P; Frings, Daniel
Abstract : Introduction: Since the advent of e-cigarettes, e-cigarette advertising has escalated and companies are able to use marketing strategies that are not permissible for tobacco products. Research into the effect of e-cigarette advertising on attitudes towards tobacco and e-cigarettes is in its infancy. To date, no research has compared indirect (implicit) measures of attitude towards e-cigarettes with direct (explicit) measures. Furthermore, little consideration has been given to how viewing online advertisements may have an effect on attitudes towards e-cigarettes or how positive attitudes to e-cigarettes may undermine antismoking public health messages. The objectives of this study are to investigate (1) the relationship between explicit and implicit attitudes towards tobacco and e-cigarettes, (2) the effect of e-cigarette advertising on these attitudes and (3) the effect of these attitudes on the efficacy of antismoking health messages. Methods and analysis: In experiment 1 an analysis of covariance will be conducted to determine whether viewing an e-cigarette advertisement, compared with a neutral image, has an effect on implicit or explicit attitudes towards tobacco and e-cigarettes, and if these attitudes differ between smokers, vapers and non-smokers aged 18 - 25 years. In experiment 2, moderation analysis will be conducted to assess whether attitudes towards e-cigarettes moderate the psychological efficacy of antismoking health messages in participants aged 18–65 years. In each experiment, attitudes will be measured preintervention and postintervention and 1 week later (n=150) in participants who are smokers (n=50), vapers (n=50) or non-smokers (n=50). Ethics and dissemination: Approval for this study has been given by the London South Bank University's (LSBU) Research Ethics Committee. The findings of these studies will be submitted for publication and disseminated via conferences. The results will be integrated into course provision for practitioners training at LSBU.